The complete chloroplast genome sequence of Aconitum austroyunnanense W. T. Wang (Ranunculaceae): a medicinal plant endemic to China. Issue 1 (2nd January 2020) - Cheng, Zi-Dan; He, Jun; Zhang, Ying-Min; Yang, Cong-Wei; Ma, Xiao-Xia; Li, Guo-Dong
Abstract: The complete chloroplast (cp) genome of Aconitum austroyunnanense W. T. Wang, a rare and endangered medicinal plant endemic to southwestern China, was sequenced to be 155, 818 bp in length, including two inverted repeat (IR, 26, 128 bp) regions, one large single-copy region (LSC) and one small single-copy region (SSC) of 86, 555 bp and 17, 007 bp, respectively. The cp genome has 131 annotated genes, including 85 protein-coding genes, 37 tRNA genes, 8 rRNA genes, and a pseudogene ( ycf1 ). The overall GC content of it is 38.1%. Phylogenetic analysis revealed that the cp genome of A. austroyunnanense is closely related to that of Aconitum hemsleyanum.